2013
DOI: 10.1002/micr.22120
|View full text |Cite
|
Sign up to set email alerts
|

Tongue reconstruction with minimal donor site morbidity using a deep inferior epigastric perforator (DIEP) free flap in a 6‐year‐old girl

Abstract: Tongue reconstruction was performed using a deep inferior epigastric perforator (DIEP) free flap in a 6-year-old girl with undifferentiated sarcoma of the tongue. After hemi-glossectomy with upper neck dissection, a 3-lobed DIEP free flap was used for the reconstruction. Donor site was closed primarily with suturing umbilicus in proper position. No flap loss, leakage, or infection occurred. Postoperatively, the patient was able to consume a normal diet without difficulty or aspiration and displayed good speech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The abdominoplasty-like transverse design is also proposed in some of the articles ( 18 , 76 , 77 ) although some variations exist. Yano et al ( 65 ) described a DIEP flap that has three lobes and a single perforator. Adding a shallow incision on the surface between the second and third lobe helps in creating a crease for three-dimensional spatial flap in-setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominoplasty-like transverse design is also proposed in some of the articles ( 18 , 76 , 77 ) although some variations exist. Yano et al ( 65 ) described a DIEP flap that has three lobes and a single perforator. Adding a shallow incision on the surface between the second and third lobe helps in creating a crease for three-dimensional spatial flap in-setting.…”
Section: Resultsmentioning
confidence: 99%
“…It is also worth noting that non-breast reconstruction using the DIEP flap is not a common technique employed by most reconstructive surgeons. Those who publish the different reports are usually from the same working groups [Yano et al ( 65 , 66 ), Zhang et al ( 67 , 75 , 104 ) or Kostakoğlu et al ( 18 , 76 )].…”
Section: Discussionmentioning
confidence: 99%
“…The SCIP flap vascularized based on the superficial branch (SB-SCIP flap) has the following advantages: decreased donor morbidity, 911 reliable vascularity, 4,12 short time for flap elevation, 1,8,13 and multiple tissue/component inclusion. 1317…”
Section: Discussionmentioning
confidence: 99%
“…Engel et al recently reported that the reconstructive goal for patients with one‐third residual tongue tissue is to maintain mobility using a thin and pliable flap. In these patients, a radial forearm free flap is widely recommended, although in thin patients, a thin perforator flap can sometimes be used instead . By contrast, patients with a total glossectomy require restoration of volume using a bulky musculocutaneous flap to prevent aspiration and achieve proper deglutition.…”
Section: Discussionmentioning
confidence: 99%